International bibliography of economics (Travistock LondonGB, 1985)
Lists the most important publications in the field of economics for each year. Pays special attention to official publications of national governments. Contains author and subject indexes and a list of periodicals consulted. Main subjects covered include inter alia, economic activity, organization of production, agricultural and industrial production, prices and markets and international economics.
Text in English and French